Lithospheric model along transect HT-1 across Western Carpathians and Pannonian Basin based on 2D integrated modelling - DÉREROVÁ, Jana; BIELIK, Miroslav; KOHÚT, Igor; GODOVÁ, Dominika; VOZÁR, Ján; BEZÁK, Vladimír (Contributions to Geophysics and Geodesy, 2020)
2D integrated modelling approach was applied to determine the lithospheric structure along transect HT-1 located in the Carpathian-Pannonian Basin–European platform region. Our approach combines simultaneous interpretation of surface heat flow, topography, gravity and geoid data. All available geophysical and geological data were used to create an initial model that has been afterwards modified by trial and error method until reasonable fit was obtained between input data and model predictions. The main focus of our study was the position and shape of the lithosphere-asthenosphere boundary (LAB). In the Pannonian Basin the modelled LAB is at depths of about 80–90 km and rapidly dips towards the Western Carpathians where its depth reaches values 145 to 150 km. Beneath the European platform the LAB depth is about 135–140 km. We can observe a slight lithospheric root under the Western Carpathians. This lithospheric thickening is interpreted as a small remnant of a subducted slab. This result is in a good agreement with the previous lithospheric models in the Carpathian-Pannonian Basin.